GEOSPATIAL PROFILING OF FLOOD VICTIMS AND ASSOCIATED LOSSES OF LIVES AND PROPERTIES IN THE AFTERMATH OF 2022 FLOODS IN JIGAWA STATE, NORTHERN NIGERIA - Tudunwada, Ibrahim Yakubu; Ahmad, Abbas (FUDMA Journal of Sciences, 2026)
Flooding is one of the natural disasters causing destructions in Jigawa state, Nigeria. Since 2018, flood has been claiming lives and properties across Jigawa. The real figures on loss of lives and properties have not been scientifically reported. The aim of this research is to conduct a geospatial profiling of flood victims and associated loss of lives and properties in the aftermath of 2022 floods in Jigawa. Fatality locations were determined through indexing and buffering using GeoEye, LandSat 8 and Shuttle Radar Topography Mission images. Extent of flooded areas in August, September and October, 2022 were determined using modified normalized difference water index. All analyses were done in ArcGIS 10.3 and SPSS. Out of the 27 Local Government Areas, 19 were affected. Areas with highest flooding were: Guri, Kirikasamma, Miga, Auyo and Ringim in descending order. Most of the flood prone areas were characterized by low elevation, proximity to water bodies and poor land use planning. Miga LGA recorded the highest number of deaths (20) followed by Kirikasamma (14) Birnin Kudu(13) Kafin Hausa(11) Jahun & Ringim (8) Birniwa (7) Auyo (6) Sule Tankarkar (4) Hadejia & Maigatari (3) Kaugama & Malammadori (2) Gagarawa & Taura (1). About 15 of the LGAs had buildings, farmlands and other structures affected. Causes of deaths were attributed to: building collapse (40%) water – borne diseases (20%) drowning in flood waters (15%) motor vehicle accidents (5) canoe – based accidents (5%) snake bites (5%) others (10%). Proper land use planning, resettlement, dredging and river trainings.